Vascular endothelial growth factor levels and rheumatic diseases of the elderly. Issue 1 (December 2016) - Smets, Perrine; Devauchelle-Pensec, Valérie; Rouzaire, Paul-Olivier; Pereira, Bruno; Andre, Marc; Soubrier, Martin
Abstract Background Increasing vascular endothelial growth factor (VEGF) has been reported in remitting symmetrical seronegative synovitis with pitting edema (RS3PE) syndrome, rheumatoid arthritis (RA), polymyalgia rheumatica (PMR) and giant cell arteritis (GCA). The aim of this study was to compare VEGF levels in patients over 60 years of age who have RS3PE, RA, PMR or GCA so as to determine whether elevated VEGF is specific for a rheumatic disease, the inflammation or edema that occurs with these pathological conditions. Methods In this retrospective, multicentric study we assessed serum and plasma levels of VEGF in patients over 60 years of age with rheumatic diseases that were eitherde novo or of recent onset according to the initial clinical presentation, and we compared these patients with a control group. Results Serum and plasma VEGF levels were determined in 80 patients (5 with RS3PE, 13 with RA, 44 with PMR, and 18 with GCA) and 37 controls. Edema occurred in five patients with RS3PE, four with RA, and one with PMR, but not patients with GCA. Serum VEGF levels were significantly higher in individuals with rheumatic diseases (849 (405.5–1235.5) pg/ml) relative to the controls (484 (302–555) pg/ml) (p < 0.001). There were no significant differences between patients with RS3PE, RA, PMR, or GCA in terms of the VEGF serum levels (p = 0.60) or plasma levels (p = 0.57). Similarly, the occurrence of edema did not correlate with VEGF levels. Conclusion VEGF increases in rheumatic diseases compared to a control group. This was not associated with specific rheumatic diseases or with edematous rheumatic diseases.